2013
DOI: 10.1185/03007995.2013.869491
|View full text |Cite
|
Sign up to set email alerts
|

High concentration capsaicin for treatment of peripheral neuropathic pain: effect on somatosensory symptoms and identification of treatment responders

Abstract: Completion of painDETECT was optional and therefore data was not available for all patients. Further studies for confirmation of these results are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 20 publications
0
19
0
4
Order By: Relevance
“…Moreover, data from a large uncontrolled general prediction study of high-concentration capsaicin patches showed that higher baseline painDETECT scores were associated with greater pain reduction after 12 weeks of treatment in patients with chronic neuropathic pain [126]. Collectively, these findings strongly suggest that specific neuropathic pain phenotypes may be associated with differential responses to varying analgesic treatments.…”
Section: Phenotypic Domainsmentioning
confidence: 99%
“…Moreover, data from a large uncontrolled general prediction study of high-concentration capsaicin patches showed that higher baseline painDETECT scores were associated with greater pain reduction after 12 weeks of treatment in patients with chronic neuropathic pain [126]. Collectively, these findings strongly suggest that specific neuropathic pain phenotypes may be associated with differential responses to varying analgesic treatments.…”
Section: Phenotypic Domainsmentioning
confidence: 99%
“…Höper et al [12] evaluated sensory neuropathic abnormalities (painDETECT questionnaire), finding that the presence of burning and pressure-evoked pain was weakly associated with treatment response. They argued that thermal hyperalgesia is difficult to interpret and thus cannot serve as a predictor of response, which could be ascribed to the fact that the painDETECT questionnaire does not distinguish between cold and heat-evoked pain.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental drug improved the NRS scores significantly, but the results regarding the PD-Q scores were not reported. Another open-label study on patients with NeP [15] used the PD-Q not only to identify NeP components (consequently, 18.3% of the patients had low PD-Q scores [<13]) but also to evaluate its severity. However, that study also did not present the results of the PD-Q scores over time, because completion of the PD-Q was optional in that study.…”
Section: Discussionmentioning
confidence: 99%
“…These correlations were also observed in the subset of 35 patients with a high PD-Q score (≥ 13) (current pain, r=0.38, p=0.03; average pain in the past 4 weeks, r=0.53, p=0.001; worst pain in the past 4 weeks, r=0.28, p=0.098). However, the and secondary endpoints [8][9][10][11][12][13]15]. The patients were asked to complete them twice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation